Increased rates of body dissatisfaction, depressive symptoms, and suicide attempts in Jamaican teens with sickle cell disease. Issue 12 (9th July 2016) - Bhatt‐Poulose, Komal; James, Kenneth; Reid, Marvin; Harrison, Abigail; Asnani, Monika
Abstract: Background: This study aims to examine the association of body image and weight perceptions with risk of depression and suicidal attempts in Jamaican adolescents with sickle cell disease (SCD). Methods: Adolescents with SCD and a national sample of Jamaican adolescents completed a questionnaire examining body image, weight perceptions, and risk for depression. Results: Perceived and desired body images were similar for both groups. Adolescents with SCD had higher levels of "negative body satisfaction" (43.9% vs. 33.9%; P = 0.03), risk for depression (28.7% vs. 19.3%; P = 0.01), and attempted suicide (12.4% vs. 6.6%; P = 0.02) than national sample. Risk of depression was higher in those who perceived themselves to be over or underweight, and lower in those with more friends and attending school. Females and those with body image dissatisfaction were more likely to have attempted suicide. Within the SCD adolescents, girls were at greater odds of having mental health issues. Conclusions: Jamaican adolescents with SCD have significantly higher rates of negative body satisfaction and depressive symptoms, and nearly twice the rate of attempted suicide, compared with their healthy peers. This underscores the need for healthcare professionals to better explore and discuss healthy weight, body satisfaction, and coping with the demands and uncertainties of having a chronic illness with Jamaican adolescents with SCD, even while promoting body acceptance and good self‐esteem. Screening for mood disorders is strongly recommended and gender‐specific interventions should be developed. Healthcare professionals need to encourage positive social interactions that improve adolescents' mental health.